Reduced Moderate-to-Vigorous Physical Activity and Increased Sedentary Behavior Are Associated With Elevated Blood Pressure Values in Children With Cerebral Palsy. Issue 8 (1st August 2014) - Ryan, Jennifer M.; Hensey, Owen; McLoughlin, Brenda; Lyons, Alan; Gormley, John
Abstract : Background: Children with cerebral palsy (CP) participate in reduced levels of physical activity and spend increased time in sedentary behavior. The effect of reduced activity and increased sedentary behavior on their cardiometabolic health has not been investigated. Objectives: The purposes of this study were: (1) to investigate the prevalence of overweight/obesity and elevated blood pressure (BP) among a cohort of ambulatory children with CP and (2) to investigate the associations among physical activity, sedentary behavior, overweight/obesity, and BP in children with CP. Study Design: This was a cross-sectional study of 90 ambulatory children, aged 6 to 17 years, with CP. Methods: Body mass index (BMI), waist circumference, waist-height ratio, and BP were measured on 1 occasion. Habitual physical activity was measured by accelerometry over 7 days. Results: The prevalence of overweight/obesity in the cohort was 18.9%. Twenty-two percent of the children had BP values within the hypertensive or prehypertensive range. Systolic BP was positively associated with waist circumference (β=.324, P <.05) and BMI (β=.249, P <.05). Elevated BP values were associated with reduced time in moderate-to-vigorous activity, vigorous activity, and total activity, as well as increased time in sedentary behavior. The strongest association was observed between elevated BP and vigorous activity alone (odds ratio=0.61, 95% confidence interval=0.37–0.99, P <.05). Limitations: A convenience sample was recruited for this study, and it is possible that this limitation resulted in selection bias. Conclusions: Despite the relatively low prevalence of overweight/obesity, a relatively high proportion of children with CP had elevated BP values. Reducing sedentary behavior and increasing habitual physical activity, particularly vigorous activity, should be primary aims of rehabilitation in order to reduce cardiometabolic disease risk in this population.